PEMAKNAAN DARI SIMBOL-SIMBOL ALAM DALAM HAIKU KARYA MATSUO BASHO DAN SHI KARYA KANAI CHOKU (SEBUAH KAJIAN SEMIOTIKA) - Dyah, Suci; Hastuti, Nur; Noviana, Fajria (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
Poetry is a literary work that has existed since long time ago. There are many types of poetry in Japanese Literature, namely, tanka, haiku, shi, kashi, and another. In this thesis, the type of Japanese poem, haiku and shi have similarity. Both of them have similarity in using natural symbols, but they have different meanings. The purpose of this thesis are to determine the meaning of haiku and shi, and also the meaning of the natural symbols in those poems. The methods that are used to analyze the meaning of the natural symbols in the poem are structural method and semiotic method. Structural method is used to analyze the structure of the physical poem and inner structure poem. Analysis of the physical structure consists of diction, imagery, concrete word, and the figure of speech. Analysis of the inner structure consists of theme, tone, atmosphere, feel, and message. This structural method is used to determine the meaning of the whole poem. Semiotic method is used to determine the meaning of the natural symbols in poem. Natural symbols consist of phenomenon of plant, animal phenomenon, phenomenon of water, air phenomenon, phenomenon of soil and other natural symbols. Results of this thesis explain that haiku describes the implicit meaning of the circumstances at the time of the Edo period. Shi explains the feelings of the author. In addition, there are twenty natural symbols that contain in haiku and shi. There are six symbols of the plant phenomena, five animal phenomena, three water phenomena, an air phenomenon, two soil phenomena, and three another natural phenomena. All symbols have different meanings.